2020
DOI: 10.1038/s41467-020-15092-4
|View full text |Cite
|
Sign up to set email alerts
|

Nanohybrids of a MXene and transition metal dichalcogenide for selective detection of volatile organic compounds

Abstract: Two-dimensional transition metal carbides/nitrides, known as MXenes, have been recently receiving attention for gas sensing. However, studies on hybridization of MXenes and 2D transition metal dichalcogenides as gas-sensing materials are relatively rare at this time. Herein, Ti 3 C 2 T x and WSe 2 are selected as model materials for hybridization and implemented toward detection of various volatile organic compounds. The Ti 3 C 2 T x /WSe 2 hybrid sensor exhibits low noise level, ultrafast response/recovery ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
292
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 405 publications
(316 citation statements)
references
References 54 publications
10
292
0
Order By: Relevance
“…[28] They have numerous applications in a variety of fields ranging from energy materials, lubricating additives, nanocomposites, etc. owing to excellent properties; [5,8,13,[28][29][30][31][32][33] MXene-based composites have already been used in many fields such as electromagnetic shielding, [32,34,35] electronics, [36] electrical and thermal conductors, [33,37,38] environmental remediations, [39] supercapacitors, [40,41] fire safety materials, [42] photocatalysts, [43,44] sensors, [10,45] batteries, [46] self-healing composites, [40,47] water purifications, [44,48] antibacterial materials, [49] actuators, [50] and other advanced materials and structures. [8,29,51] For instance, Kang et al [36] developed Ti 3 C 2 MXene reinforced epoxy nanocomposite to enhance thermal and electrical performance wherein they found that the addition of 1.0 wt% few-layer Ti 3 C 2 MXene increases the thermal conductivity to 0.587 W m −1 K −1 , attaining 141.3% improvement compared with that of unreinforced sample.…”
Section: Introductionmentioning
confidence: 99%
“…[28] They have numerous applications in a variety of fields ranging from energy materials, lubricating additives, nanocomposites, etc. owing to excellent properties; [5,8,13,[28][29][30][31][32][33] MXene-based composites have already been used in many fields such as electromagnetic shielding, [32,34,35] electronics, [36] electrical and thermal conductors, [33,37,38] environmental remediations, [39] supercapacitors, [40,41] fire safety materials, [42] photocatalysts, [43,44] sensors, [10,45] batteries, [46] self-healing composites, [40,47] water purifications, [44,48] antibacterial materials, [49] actuators, [50] and other advanced materials and structures. [8,29,51] For instance, Kang et al [36] developed Ti 3 C 2 MXene reinforced epoxy nanocomposite to enhance thermal and electrical performance wherein they found that the addition of 1.0 wt% few-layer Ti 3 C 2 MXene increases the thermal conductivity to 0.587 W m −1 K −1 , attaining 141.3% improvement compared with that of unreinforced sample.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of abundant groups on its surface makes it hydrophilic, but increasing the groups, electric conductivity decreases. The activated metallic hydroxide sites, large surface to volume ratio, high melting point, high thermal conductivity, exceptional hardness, ultra-thin, good oxidation resistance serves MXene as excellent material in several fields, such as field-effect transistor 26 , water purification 27 , chemical sensors 28 , biosensors 29 , detection of volatile organic compounds 30 , photo/electro-catalysis (e.g., photocatalytic hydrogen production 31 , photocatalytic for nitrogen fixation 32 , CO 2 reduction activity), energy conversion devices (including triboelectric nanogenerators, solar fuel generation and water splitting) [33][34][35][36] , capacitive desalination 37 , biomedical 38 , energy storage (including batteries and supercapacitors), spintronics, nano-electronic/optoelectronics, and topological applications 30,32,39,40 . The lateral dimension range of MXenes is from nanometers to micrometers; else, the thickness can be found in the nanometer range 41 .…”
Section: Introductionmentioning
confidence: 99%
“…Besides MOX- and GO-based 2D materials, it is important to mention other emerging materials with the same dimensionality that have a significant role in VOCs detection, although not the scope of this review. Among them are 2D transition metal dichalcogenides (TMDs) with their unique physical and chemical properties, such as a high surface-to-volume ratio, large number of active sites for redox reactions, high surface reactivity, and high absorption coefficient [ 86 ]. These materials have the formula MX 2 , where M stands for transition metal element (e.g., Ti, Zr, Hf, V, Nb, Ta, Mo, W, Re, etc.)…”
Section: Tailoring Materials For Enhanced Sensing Properties To Vomentioning
confidence: 99%
“…and X represents a chalcogen (Se, S, or Te) [ 87 ]. Some of the most common TMDs for VOCs detection are MoS 2 , WS 2 , MoSe 2 , WSe 2 , and SnS 2 [ 86 , 88 , 89 , 90 , 91 ].…”
Section: Tailoring Materials For Enhanced Sensing Properties To Vomentioning
confidence: 99%
See 1 more Smart Citation